Efficacy of a Tibia Counter Rotator System for the Treatment of Internal Tibial Torsion in Children - Sungmi Kim; Mitsuyoshi Suzuki; Kei Minowa; Hiroshi Nittono; Toshiaki Shimizu (MDPI AG, 2022)
Internal tibial torsion is more common in the Asian population than in Western populations. Generally, surgery should be considered for the treatment of severe internal tibial torsion. As an alternative approach, the usefulness of a tibia counter rotator (TCR), a corrective orthosis based on the theory of the tibia torsional transformer, has been demonstrated, but the evidence is limited. In the present study, the efficacy and safety of TCR treatment were investigated in pediatric patients with internal tibial torsion. The subjects were 124 pediatric patients with internal tibial torsion who were between 3 and 15 years of age and had no underlying diseases. The severity of tibial intorsion was evaluated by the tibial transmalleolar angle (TMA). A TMA less than 5° was defined as internal tibial torsion, and less than −20° was defined as severe in this study. The median duration of TCR use was 11 (9, 12) (median (IQR: interquartile range)) months, and the treatment completion rate was 94.4% (117/124). The TMA at 12 months from the start of treatment in patients who completed treatment was 5° (0°, 10°) on the right (n = 66) (p < 0.01 vs. pretreatment) and 0° (−5°, 8°) on the left (n = 71) (p < 0.01 vs. pretreatment). The tibial torsional transformer used in this study is effective in the initial treatment of mild to severe internal tibial torsion, with no adverse effects. Although internal tibial torsion is generally expected to resolve spontaneously, TCR treatment may be an effective alternative to surgical therapy in the Asian pediatric population.